Low Frequency Severe-Intensity Interval Training Markedly Alters Respiratory Compensation Point During Incremental Exercise in Untrained Male - Nakahara, Hidehiro; Ueda, Shin-ya; Miyamoto, Tadayoshi (Frontiers in Physiology, 2020)
This study investigated the effect of low-frequency severe-intensity interval training on the respiratory compensation point (RCP) during incremental exercise test. Eighteen healthy males (age; 20.7 ± 2.2 years, range 18 to 29 years, height; 174.0 ± 5.6 cm, weight; 68.8 ± 13.5 kg) were randomly assigned to an interval training group or a control group. Interval training was conducted once weekly for 3 months. Each session consisted of three bouts of bicycle ergometer exercise at 80% maximum work rate until volitional fatigue. Before (baseline) and after the 3-month intervention, incremental exercise test was performed on a bicycle ergometer for determination of ventilatory threshold (VT), RCP, and peak oxygen consumption (V(・)O2 peak). The training program resulted in significant increases of V(・)O2 peak (+14%, p<0.001, ȠP2= 0.437), oxygen consumption (V(・)O2) at VT (+18%, p<0.001, ȠP2= 0.749) and RCP (+15%, p=0.03, ȠP2= 0.239) during incremental exercise test in the training group. Furthermore, a significant positive correlation was observed between the increase in V(・)O2 peak and increase in V(・)O2 at RCP after intervention (r=0.87, p=0.002) in the training group. Tidal volumes at VT (p=0.04, ȠP2= 0.270) and RCP (p=0.01, ȠP2= 0.370) also increased significantly after intervention compared to baseline. Low-frequency severe-intensity interval training induced a shift in RCP toward higher work rate accompanied by higher tidal volume during incremental exercise test.